n(A) = 5, n(A ∪ B) = 7, and n(B) = 5,
then what is
n(A ∩ B)?
Thank you for the opportunity to help you with your question!
we know that n(AUB)=n(A)+n(B)-n(A∩ B)
thus n(A∩ B)=(5+7)-7=2
I guarantee the answer is 100% correct, best me please thanks
Can you please explain how you solved this?
you have to know the formula n(AUB)=n(A)+n(B)-n(A∩ B) first, then all you have to do is to plug in the numbers.
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?